PETUNJUK RASULULLAH SAW TENTANG HAK PENDIDIK - Abdul Wahab Syakhrani; Ridha Rahmatina; Sri Ayu Rahmadani; Yurianah Yurianah (CV. ADIBA ASIHA AMIRA, 2022)
An educator who is diligent and active without complaining in teaching will be given respect and appreciation for all his services. This award can be in the form of praise, thanks, better rewards, prayers and so on. Scholars agree on the permissibility of taking rations from the baitul-maal as wages for teaching the Qur'an, or also teaching other sharia sciences such as hadith, interpretation, fiqh and others. The wages taken from the baitul-maal are actually not payments for this knowledge, but rather as a form of helping each other in obedience (worship), and that does not change the value of the teaching worship. With this